Delayed Union of Fractures of Both Bones of the Forearm - Osako, Y.; Yamamoto, K. (Orthopedics & Traumatology, 1973)
With regard to delayed or non-union, fifty-eight fractures of both bones of the forearm were reviewed at our orthopaedic department during twenty years from 1953 to 1972, and thirteen cases were found to be unsatisfactorily united after initial treatment. The incidence of delayed union was 22.4per cent. All the patients were over the age of fifteen and no delayed union were occured in children. Twelve patients with delayed uniou had been operated as initial treatment, but the operative techinique varied in each cases, fixation by wires, screws, plates and intramededullary rods. All the delayed union occured iu fractures of middle third of both bones of the forearm. The f actores most affective to delayed union of fractures were incorrect techinique of bone fixation. The common errors were lack of rigid fixation, too small of intramedullary rods, unsatisfacotry reduction, especially in pronated position, and no combinatioin with bone grafting. Early mobilization was also conductve to delayed union particularlly of fractures of both hones of the forearm. All cases were related to inadequate surgery and after treatment. There is no doubt that in the surgery of fractures of both bones of the froearm the important principles are rigid fixation, reduction into anatomical correct position, and that bone grafting sholudld be combined in cases of adult. Usually immobililization should be continued for a minimum of three or four months after the operation.